The Digital Revolution as a Effort to Build a New Economic Narrative - Endah Fantini; Samsudin Samsudin (Yayasan Ilomata, 2022)
Environmental pollution and climate damage are certainly a serious problem for most people because their impact can threaten the survival of the ecosystem of creatures and humans themselves. So this needs to be anticipated regarding the effects of carbon, gas emissions, and the greenhouse effect, all of which have replaced the operational systems of analog or manual devices with electronic devices, especially digital-based electronic devices that are environmentally friendly and have the potential to maintain economic stability with new patterns and methods. digitally based.